12 - A Life Course and Cross-Level Approach to the Study of HIV/Aids in Africa - Seck, Berhane Berhe Araia (CODESRIA Bulletin, 2003)
The social science approach to HIV/Aids research has been tilted excessively in favour of socio-cultural behavioural issues which can distort and mislead. Reviewing the literature on HIV/Aids in sub-Saharan Africa reveals that much of the problem emanates from the lack of an integrated approach, one that simultaneously takes into account the different levels of social life and the timing of events in individuals’ age groups and historical periods. I argue in this paper for an approach that follows a life course perspective. This assumes that the interaction between culture and individual behaviour is mediated by historical location, social relationships, and the life stages of individuals and groups. I therefore propose a research design for the study of HIV/Aids based on this perspective, arguing for a multilevel approach that makes use of available information from demographic and health surveys. I provide some examples of how this approach might work and conclude with suggestions for comparative research studies of HIV/Aids in Africa.